Evolutionary Analysis of Unicellular Species in Chlamydomonadales Through Chloroplast Genome Comparison With the Colonial Volvocine Algae - Hu, Yuxin; Xing, Weiyue; Song, Huiyin; Zhu, Huan; Liu, Guoxiang; Hu, Zhengyu (Frontiers in Microbiology, 2019)
This study is the first determination of six chloroplast genomes of colonial volvocine algae, Colemanosphaera charkowiensis, Volvulina compacta, Pandorina colemaniae, Pandorina morum, Colemanosphaera angeleri and Yamagishiella unicocca. Based on 55 chloroplast protein-coding genes, we compared the nonsynonymous (dN) and synonymous (dS) substitution rates between colonial volvocine algae and the other unicellular Chlamydomonadales species. When refer to the dN, we found 27 genes were significantly different, among them, 19 genes were significant higher in unicellular species (FDR-adjusted P value < 0.05). When refer to the dS, we found 10 genes were significantly different, among them, 6 genes were significant higher in unicellular species (FDR-adjusted P value < 0.05). Then we identified 14 putative fast-evolving genes and 11 putative positively selected genes of unicellular species, we analyzed the function of positively selected sites of the overlap genes of putative fast-evolving and positively selected genes, and found some sites were close to the important functional region of the proteins. Photosynthesis is the process to transform and store solar energy by chloroplast, it plays a vital role in the survival of algae, this study is the first to use the chloroplast genomes to analysis the evolutionary relationship between colonial and unicellular species in Chlamydomonadales. We found more genes have higher substitution rates in unicellular species and proposed that the fast-evolving and positively selected two genes, psbA and psbC, may help to improve the photosynthetic efficiency of unicellular species in Chlamydomonadales.